2019
DOI: 10.1016/j.isci.2019.03.028
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY-Decorated Nanoscale Covalent Organic Frameworks for Photodynamic Therapy

Abstract: HIGHLIGHTS Covalent organic frameworks (COFs) are first used in tumor photodynamic therapy BODIPY-decorated COFs are synthesized via bonding defects functionalization BODIPY-decorated COFs have excellent anti-tumor efficacy in vitro and in vivo COFs show great promise as nanoplatforms for biomedical applications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
135
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 146 publications
(147 reference statements)
2
135
0
Order By: Relevance
“…The PDT effect of traditional PSs (such as porphyrin BODIPY) is usually limited by low cell uptake owing to their poor aqueous solubility. As reported in previous studies, modification or loading of PSs onto nanocarriers can overcome these deficiencies and thus improve antitumor therapy.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…The PDT effect of traditional PSs (such as porphyrin BODIPY) is usually limited by low cell uptake owing to their poor aqueous solubility. As reported in previous studies, modification or loading of PSs onto nanocarriers can overcome these deficiencies and thus improve antitumor therapy.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Dichtel's and Bein's groups employed monomer‐truncation strategy to create defects for functionalization of COFs. Meanwhile, Yaghi's, Lotsch's, Loh's, and Dong's groups constructed defective COFs via precise controlling the reaction solvent and conditions. As a whole, introducing defects into COFs maybe a good method for enlarging applications and tailoring structures of COFs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yaghi's and Lotsch's groups obtained COFs with free amine groups, but have not been utilized for further postfunctionalization. Dong's group prepared NCOFs with free terminal aldehyde groups as anchoring sites for postfunctionalization . However, although several examples have been reported about COFs containing free amine or aldehyde groups, the researches on these two anchoring sites for further functionalization are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[4e,6] Recently,t he well-known functional motif boron-dipyrromethene (BODIPY) was also grafted into COF pores to introduce PDT activity. [7] However,i na ll these studies,t he molecular building block selected for the structural design exhibited ROSa ctivity on their own, while inactive functional motifs were left largely unexplored. Herein, we demonstrated that, for the first time,m olecules incapable of generating ROSb y themselves can also be utilized for the construction of an extended porous framework to give efficient ROSproduction capability.Given the large variety in the choice of molecular building blocks and merits of COFs as an ew generation of nanocarriers, [8] this method provides an extra tool for the design of molecular PS to achieving desirable PDT performance.C OF-909, constructed by linking 4,4',4''-(1,4-phenylene)bis(([2,2':6',2''-terpyridine]-5,5''-dicarbaldehyde)) (L-3N), exhibited ab and gap of 1.96 eV,s howed an excellent overlap with that of the superoxide,t hus leading to drastic promotion in ROS generation performance.T he ROSg eneration rate of COF-909 is three times better than the stateof-the-art porphyrin based PSs,t etra(4-carboxyphenyl) porphyrin (TCPP).…”
mentioning
confidence: 99%